Insulin and mTOR Pathway Regulate HDAC3-Mediated Deacetylation and Activation of PGK1: e1002243 - Wang, Shiwen; Jiang, Bowen; Zhang, Tengfei; Liu, Lixia; Wang, Yi; Wang, Yiping; Chen, Xiufei; Lin, Huaipeng; Zhou, Lisha; Xia, Yukun; Chen, Leilei; Yang, Chen; et al. (PLoS biology, 2015)
Phosphoglycerate kinase 1 (PGK1) catalyzes the reversible transfer of a phosphoryl group from 1, 3-bisphosphoglycerate (1, 3-BPG) to ADP, producing 3-phosphoglycerate (3-PG) and ATP. PGK1 plays a key role in coordinating glycolytic energy production with one-carbon metabolism, serine biosynthesis, and cellular redox regulation. Here, we report that PGK1 is acetylated at lysine 220 (K220), which inhibits PGK1 activity by disrupting the binding with its substrate, ADP. We have identified KAT9 and HDAC3 as the potential acetyltransferase and deacetylase, respectively, for PGK1. Insulin promotes K220 deacetylation to stimulate PGK1 activity. We show that the PI3K/AKT/mTOR pathway regulates HDAC3 S424 phosphorylation, which promotes HDAC3-PGK1 interaction and PGK1 K220 deacetylation. Our study uncovers a previously unknown mechanism for the insulin and mTOR pathway in regulation of glycolytic ATP production and cellular redox potential via HDAC3-mediated PGK1 deacetylation.